KONSTRUKSI REALITAS MEDIA MASSA TEMPO DAN REPUBLIKA DALAM PEMBERITAAN BASUKI TJAHAJA PURNAMA PASCA PILKADA PUTARAN PERTAMA DKI JAKARTA 2017 - Onny Safwedha; Taufik Suprihatini (Interaksi Online, 2019)
The results of the study show that the redactional policies of each medium affect the viewpoint taken in the news of an event. The redactional policy taken by Tempo, makes Tempo look to strive more objectively in performing news. Tempo provided fairly neutral and balanced reverence and criticism, such as Tempo's mission as an independent medium. Tempo and Republika have slightly different redactional policies in conducting an information of the Full Tjahaja Basuki. Furthermore, Republika provides inclined preaching in a more Islamic point of view, such as the Republika mission to put the interests of Muslims first. The results of the research that Tempo tended to display balanced information or equally large information from both pro- and con-parties. Compared to a Republika that tends to be heavy on one side, because it adores an Islamist preaching.